Pola Fungsi Kalimat pada Novel “Pulang” Karya Tere Liye dan Kelayakannya sebagai Materi Pengayaan Siswa Kelas Xll SMA - Muchammad Akbar Ibrani; Angelica Hexa Trinita Pandiangan; Titis Abhirama Reswara; Moch. Yusuf Ilham Noer; Haula Inayatul Ilahiyah; Asep Purwo Yudi Utomo; Qurrota Ayu Neina (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Understanding sentence function patterns plays a major role in reading a novel, especially in class XII. By studying the understanding of sentence function patterns, class XII students can understand the important role of sentence function patterns in a novel. This research aims to be an informative and interesting learning resource for class XII students to use novels as enrichment material and improve their language skills. This research considers the function patterns of sentences in the novel "Pulang" by Tere Liye and the feasibility of sentence readability as enrichment material for class XII students. The method used in this research is a qualitative-descriptive method. Qualitative descriptive methods do not rely on evidence-based systematic logic, numerical principles, or statistical methods. This research helps determine the function patterns of sentences through the functions, categories, and roles of sentences in the novel, as well as the data and data sources in this research in the form of collections of sentences in the novel "Pulang" by Tere Liye. The data analysis technique used in this research uses the AGH method. The results of this research found sentence function patterns in the novel "Pulang" by Tere Liye. There are two S-P sentence patterns; there are three S-P-O sentence patterns; there are three S-P-Pel sentence patterns; there are four S-P-O-Pel sentence patterns; there are three S-P-K sentence patterns; there are four S-P-O-K sentence patterns; there are five S-P-O-Pel-K sentence patterns; and there are five S-P-O-Pel-K sentence patterns. Analysis of sentences based on function found the following sentence function patterns: S, P, O, and K. Analysis of sentences based on categories found in sentences is as follows: Function S is in the noun category. Function P is categorized as an adjective or verb. Function O is in the noun category. Ket functions are categorized as verbs, adjectives, and verb phrases. The analysis of sentences based on the roles found in the sentences is as follows: S's function is to act as an actor. Function P acts as a command or action. Function O acts as a sufferer. The functions of information are time, nature, and circumstances. Apart from that, the sentence function patterns in the novel "Pulang" by Tere Liye are suitable as enrichment material for class not good, accuracy in finding sentence function patterns, inaccuracy in finding sentence function patterns, accuracy in preparing sentence function patterns, inaccuracy in preparing sentence function patterns, effectiveness in reading story text narratives in novels, and ineffectiveness in reading story text narratives in novels. The results of this research can provide knowledge and insight into an understanding of In this research, understanding sentence function patterns for class XII students is very important to ensure that the teaching materials presented can be understood and applied by the class.